The twin-block appliance for correction of class II division 1 malocclusion. (2nd July 2021) - Salloum, Erfan; Millett, Declan T; McIntyre, Grant T
Abstract : The twin-block appliance is a widely used functional appliance for the correction of Class II division 1 malocclusion in growing children and adolescents. This article outlines the indications and case assessment, the steps in clinical management and appliance design. Evidence regarding the mode of action, effects and prediction of treatment outcome of the twin-block appliance for Class II division 1 malocclusion are also presented. CPD/Clinical Relevance: The twin-block appliance is a widely used functional appliance in the UK for the correction of Class II division 1 malocclusion in growing children and adolescents.